2017
DOI: 10.3171/2016.9.jns16559
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features and surgical outcomes of patients with skull base chordoma: a retrospective analysis of 238 patients

Abstract: OBJECTIVE Skull base chordoma is relatively rare, and a limited number of reports have been published regarding its clinical features. Moreover, the factors associated with extent of resection, as well as the value of marginal resection for long-term survival, are still in question for this disease. The objective of this study was to investigate these factors by evaluating their clinical features and surgical outcomes. METHODS A retrospective analysis of 238 patients with skull base chordomas, who met the incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
61
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(67 citation statements)
references
References 33 publications
(81 reference statements)
6
61
0
Order By: Relevance
“…In case of chordomas which origin from extracranial, we can totally or subtotally resect the tumor through an endoscopic endonasal approach without traction or exposure of the brain tissue. The total/subtotal resection rate of chordomas in this group was 66.8%, and the incidence of complications was lower than that reported in the literature [28]. Most chordomas originated from the clivus and presented with a variety of different sizes, locations, and tumor texture consistency and blood supply.…”
Section: Innovative Technologymentioning
confidence: 49%
“…In case of chordomas which origin from extracranial, we can totally or subtotally resect the tumor through an endoscopic endonasal approach without traction or exposure of the brain tissue. The total/subtotal resection rate of chordomas in this group was 66.8%, and the incidence of complications was lower than that reported in the literature [28]. Most chordomas originated from the clivus and presented with a variety of different sizes, locations, and tumor texture consistency and blood supply.…”
Section: Innovative Technologymentioning
confidence: 49%
“…When the tumor was mainly located in the paramedian region, we chose the MLOA. The resection rate was divided into four grades according to the postsurgical MRI and CT combined with the intraoperative impressions of surgeons [30]. Gross-total resection (GTR) indicated that the entire tumor was resected, the surrounding heathy tissue was obviously exposed, and no suspected tumor could be found on postsurgical images.…”
Section: Surgical Methodsmentioning
confidence: 99%
“…No residual tumor was found during surgery, and > 90% tumoral resection on images was de ned as near-total resection (NTR); > 70% tumoral resection on images was de ned as subtotal resection (STR), and a lesser extent of resection was de ned as partial resection (PR). For the sake of comparison, GTR and NTR were pooled and classi ed as marginal resection, and STR and PR were classi ed as intralesional resection [30,24,25].…”
Section: Surgical Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…With the development of modern endoscopic techniques, more and more studies have started to emerge in the world literature regarding the experience of surgical removal of centrally located tumors of the base of the skull using the endoscopic transclival approach [10][11][12][13][14][15][16][17][18][19][20]. According to Sanmillan et al [15], the results of using the endoscopic transclival approach for the removal of central tumors of the skull base are comparable to the results of using various transcranial approaches, and in a number of cases, they are clearly superior.…”
Section: Introductionmentioning
confidence: 99%